2021
DOI: 10.1155/2021/5530149
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Tai Chi on Patients with Mild Cognitive Impairment: A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background and Purpose. Mild cognitive impairment (MCI) is a common condition, which threatens the quality of life of older adults. Tai Chi (TC) is growing in popularity among patients with MCI. This study is aimed at evaluating the effectiveness and safety of TC in older adults with MCI. Design. Randomized controlled trials (RCTs) from multiple databases from inception to December 2020 published in English were searched. Two researchers independently performed eligible study screening and data extraction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
(138 reference statements)
1
25
0
Order By: Relevance
“…While the cognitive health benefits of Tai Ji Quan for cognitively intact and impaired older adults have been documented [ 16 18 ], to our knowledge this is one of the few studies that have considered Tai Ji Quan training with explicit integration of cognitive-motor dual-task performance and practice. Previously, we have shown the feasibility of an augmented dual-task Tai Ji Quan intervention for balance training and falls prevention for older adults with MCI [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the cognitive health benefits of Tai Ji Quan for cognitively intact and impaired older adults have been documented [ 16 18 ], to our knowledge this is one of the few studies that have considered Tai Ji Quan training with explicit integration of cognitive-motor dual-task performance and practice. Previously, we have shown the feasibility of an augmented dual-task Tai Ji Quan intervention for balance training and falls prevention for older adults with MCI [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the cognitive benefits may be further enhanced through integration of concurrent cognitive and motor task activities, that is, dual-task training [ 11 13 ]. In this respect, Tai Ji Quan, which requires a significant amount of cognitive effort allocated to the performance and mastery of intricate whole-body movements [ 14 , 15 ], appears to fit well as a cognitive and motor training therapy for preventing or mitigating memory loss and cognitive decline among older adults with MCI [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 3 SRs/MAs [ 32 – 34 ], the intervention method for the control group was CT or daily life activities, while that for the experimental group was TC exercise. In terms of quality evaluation scales, 6 SRs/MAs [ 27 , 29 , 30 , 32 – 34 ] used the Cochrane risk of bias standard, and 2 SRs/MAs [ 28 , 31 ] used the Physiotherapy Evidence Database scale.…”
Section: Resultsmentioning
confidence: 99%
“…By using AMSTAR-2 to assess the methodological quality, all SRs/MAs were considered to be of very low quality because more than one key item was missing from the included SRs/MAs. The restrictions came from the following items: Item 2 (only 2 SRs/MAs [ 29 , 30 ] have registered protocol), Item 7 (the list of excluded studies was not mentioned by any SR/MA), Item 10 (none reported the funding of RCTs included in SRs/MAs), and Item 15 (only one SR/MA [ 31 ] conducted publication bias assessment or discussed their impact on SR/MA). The AMSTAR-2 assessment breakdown for each SR/MA is shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation